The effects of climate fluctuations and soil heterogeneity on the floristic composition of sown Mediterranean annual pastures - Aguiar, Carlos (2014)
Sown Biodiverse Permanent Pastures Rich in Legumes (SBPPRL) is a pasture system for Mediterranean climatic areas mixing a large number of pastures species and cultivars, with a predominance of Trifolium subterraneum. Since the nineties, it rapidly expanded in Portugal due to its high dry matter yields (DM) and C sequestration rates in soil organic matter. Although without clear experimental evidence, it is currently admitted that SBPPRL are able to adjust soil spatial heterogeneity and to reflect interannual climate fluctuations. The study was realised on a SBPPRL sown in 2001on a mixed farm located in “Serra da Estrela”, the main agricultural mountain system of Portugal. The effects of two explanatory variables – “Year-climate” (moderately dry in 2007-2008 and humid in 2009-2010) and “Slope” (three positions: hill shoulder, backslope and footslope) – on the floristic composition were explored. Three botanical levels of analysis were used: all species, sown species and T. subterraneum cultivar levels. The statistical significance and the influence of the two explanatory variables on the plant composition varied between these three levels. The distribution of T. subterraneum cultivars along the microtopographical gradient was congruent with their life cycle duration: short-cycle cultivars had higher relative cover in uphill plots while longer cycle cultivars tended to dominate down the slope. Diversifying the sown species/cultivar colonists’ pool in seed pasture mixtures appears to favour microtopographic gradients and interannual climatic fluctuation tracking. Sown species diversity and T. subterraneum cultivar diversity are complementary in this process; they promote, respectively, interannual climatic and microtopographic gradients fluctuation tracking.